The Impact of Halogen Substituents on the Synthesis and Structure of Co-Crystals of Pyridine Amides - Abeysekera, Amila M. (Molecules, 2021)
Strategies for co-crystal synthesis tend to employ either hydrogen- or halogen-bonds between different molecules. However, when both interactions are present, the structural influence that they may exert on the resulting assembly is difficult to predict a priori. To shed some light on this supramolecular challenge, we attempted to co-crystallize ten aliphatic dicarboxylic acids (co-formers) with three groups of target molecules; N-(pyridin-2-yl)picolinamides (2Pyr-X), N-(pyridin-2-yl)nicotinamides (3Pyr-X), N-(pyridin-2-yl)isonicotinamides (4Pyr-X); X=Cl/ Br/ I. The structural outcomes were compared with co-crystals prepared from the non-halogenated targets. As expected, none of the reactions with 2Pyr-X produced co-crystals due to the presence of a very stable intramolecular N-H···N hydrogen bond. In the 3Pyr series, all six structures obtained showed the same synthons, –COOH···N(py) and –COOH···N(py)-NH, that were found in the non-halogenated parent 3Pyr and were additionally accompanied by structure directing X···O(OH) interactions (X=Br/I). The co-crystals of the unhalogenated parent 4Pyr co-crystals assembled via intermolecular –COOH···N(py) and –COOH···N(py)-NH synthons. Three of the analogues 4Pyr-X co-crystals displayed only COOH···N(py) and –COOH···N(py)-NH interactions. The three co-crystals of 4Pyr-X with fumaric acid (for which no analogues structures with 4Pyr are known) formed –COOH···N(py)-NH and –NH···O=C hydrogen bonds and showed no structure-directing halogen bonds. In three co-crystals of 4Pyr-I in which –COOH···N(py)-NH hydrogen bond was present, a halogen-bond based –I···N(py) synthon replaced the –COOH···N(py) motif observed in the parent structures. The structural influence of the halogen atoms increased in the order of Cl < Br < I, as the size of σ-holes increased. Finally, it is noteworthy that isostructurality among structures of the homomeric targets was not translated to structural similarities between their respective co-crystals.